PENGARUH LIFESTYLE DAN REFERENCE GROUP TERHADAP KEPUTUSAN PEMBELIAN DAN DAMPAKNYA TERHADAP KEPUASAN KONSUMEN PADA GENERASI Z PENGGUNA IPHONE DI KOTA PEKANBARU - Pramesta Arie; Restuti Sri; Musfar Firli Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Along with people's needs in the use of smartphones which is increasing, making people's buying interest in smartphones is increasing, this is due to the impact of the era of globalization which has brought many changes in human life, especially in the field of technology. This change helps humans a lot in doing things effectively and efficiently. Smartphones are mobile phones that have high-level capabilities and have functions similar to computers. Some people think of a smartphone as a phone that has advanced features and works using the entire operating system software that provides a standard and basic relationship for application developers. Therefore, this study will discuss the influence of lifestyle and reference group on purchasing decisions and their impact on consumer satisfaction in generation z iPhone users in the city of Pekanbaru. The number of respondents in this study were 126 people with the sampling method using the Non Probability Sampling technique by means of Purposive Sampling. The analytical method used in this research is SEM-PLS. The results obtained are Lifestyle variables have a positive influence on iPhone purchasing decisions in Generation Z in Pekanbaru City. Then the Reference Group variable has a positive influence on the iPhone purchase decision variable in Generation Z in Pekanbaru City. Then the purchase decision variable has a positive influence on the iPhone Consumer Satisfaction variable in Generation Z in Pekanbaru City. Then the Lifestyle variable has a positive influence on the Consumer Satisfaction variable through the iPhone purchase decision variable in Generation Z in Pekanbaru City. Then the Reference Group variable has a positive influence on the Consumer Satisfaction variable through the iPhone purchase decision variable in Generation Z in Pekanbaru City.Keywords: lifestyle, reference group, purchasing decisions, consumer satisfaction, Respondents, Significant.